Estimating the growth effects of 2004 Eastern enlargement of the European Union - Andrzej Cieślik; Mehmet Burak Turgut (Journal of Risk and Financial Management, 2021)
In this paper, we study the growth effects of the 2004 Eastern enlargement of the European Union (EU) using the synthetic control method. We estimate that this EU enlargement had an immediate but modest positive impact on the economic growth of the EU-8 countries in the first few years following their EU accession. The positive impact of the EU enlargement became more apparent from 2007 when the new EU member states were admitted into the Schengen zone. As a result, the gross domestic product (GDP) per capita difference between the actual and synthetic EU-8 continued to grow towards the end of the sample period. We found that over the entire 2004-2012 period, GDP per capita of the EU-8 was increased by about 2313 USD per year on average relative to the synthetic EU-8. The growth rate of the GDP per capita in the actual EU-8 for the same period was 2.7% larger than the synthetic EU-8.
Keywords: 330; Eastern enlargement; economic growth; European Union; synthetic control method